1997
DOI: 10.1097/00006454-199709000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia pneumoniae in acute otitis media

Abstract: This is the first study to report the isolation of C. pneumoniae in middle ear fluid of children with AOM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 24 publications
3
23
2
Order By: Relevance
“…It has been suggested that a PCR which is positive for C. pneumoniae in respiratory samples does not always indicate acute C. pneumoniae infections because there may be transient carriage of C. pneumoniae in the [3][4][5][6][7][8][9][10] The presence of only C. pneumoniae DNA in upper respiratory tract specimens, as demonstrated by the PCR, without a concomitant serological response, may indicate prolonged, harmless colonization of the respiratory tract rather than the agent causing respiratory tract infections. Therefore, conventional PCR assays cannot differentiate between acute C. pneumoniae infections and persistent ones or nasopharyngeal carriage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that a PCR which is positive for C. pneumoniae in respiratory samples does not always indicate acute C. pneumoniae infections because there may be transient carriage of C. pneumoniae in the [3][4][5][6][7][8][9][10] The presence of only C. pneumoniae DNA in upper respiratory tract specimens, as demonstrated by the PCR, without a concomitant serological response, may indicate prolonged, harmless colonization of the respiratory tract rather than the agent causing respiratory tract infections. Therefore, conventional PCR assays cannot differentiate between acute C. pneumoniae infections and persistent ones or nasopharyngeal carriage.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The PCR assays have detected persistent infections of C. pneumoniae, indicating that the majority of C. pneumoniae infections are asymptomatic. [3][4][5][6][7][8][9][10] Transient carriage without serological response seems to be a common phenomenon in younger children. These fi ndings indicate that PCR assays cannot differentiate between acute C. pneumoniae infections and persistent ones or nasopharyngeal carriage.…”
Section: Introductionmentioning
confidence: 99%
“…Both clinical data [20] and personal clinical experience with tympanocentesis show that bullous myringitis is not caused by M. pneumoniae, even when MEE are tested with more sensitive PCR assays for that pathogen (0 of 50 patients). In contrast, Block et al [41] have isolated Chlamydia pneumoniae from a small but significant percentage (8% of 101 children) with AOM. Five of the children with this pathogen were very young (8 to 17 months old) and 3 had refractory AOM.…”
Section: Other Pathogens Of Aommentioning
confidence: 92%
“…In contrast, Block et al [9] recovered C. pneumoniae from the middle-ear fluids of eight of 101 (8%) children (3 months to 14 years of age) with AOM. None of the children, five of whom were younger than 16 months of age, had C. pneumoniae recovered from their nasopharyngeal culture.…”
Section: Otitis Mediamentioning
confidence: 94%